Ivacaftor pharmacokinetics and lymphatic transport after enteral administration in rats - Pozniak, Jiří; Ryšánek, Pavel; Smrčka, David; Kozlík, Petr; Křížek, Tomáš; Šmardová, Jaroslava; Nováková, Anežka; Das, Debanjan; Bobek, Daniel; Arora, Mahak; Hofmann, Jiří; Doušová, Tereza; et al. (Frontiers in Pharmacology, 2024)
Background: Ivacaftor is a modern drug used in the treatment of cystic fibrosis. It is highly lipophilic and exhibits a strong positive food effect. These characteristics can be potentially connected to a pronounced lymphatic transport after oral administration. Methods: A series of studies was conducted to describe the basic pharmacokinetic parameters of ivacaftor in jugular vein cannulated rats when dosed in two distinct formulations: an aqueous suspension and an oil solution. Additionally, an anesthetized mesenteric lymph duct cannulated rat model was studied to precisely assess the extent of lymphatic transport. Results: Mean ± SD ivacaftor oral bioavailability was 18.4 ± 3.2% and 16.2 ± 7.8%, respectively, when administered as an aqueous suspension and an oil solution. The relative contribution of the lymphatic transport to the overall bioavailability was 5.91 ± 1.61% and 4.35 ± 1.84%, respectively. Conclusion: Lymphatic transport plays only a minor role in the process of ivacaftor intestinal absorption, and other factors are, therefore, responsible for its pronounced positive food effect.